THE REPRESENTATION OF THE MAPPING CLASS GROUP OF A SURFACE ON ITS FUNDAMENTAL GROUP IN STABLE HOMOLOGY - Tillmann, U (2010)
The natural action of the mapping class group of an orientable or non-orientable surface on its fundamental group induces a group homomorphism into the automorphism group of a free group. In the light of a recent theorem, we determine here the map on stable homology. © 2009. Published by Oxford University Press. All rights reserved.